Development of green photocatalytic geopolymers for dye removal - Asim N.; Badiei M.; Shakeri M.; Emdadi Z.; Samsudin N.A.; Soltani S.; Mohammad M.; Amin N. (Elsevier Ltd, 2023)
Adsorption; Aromatic compounds; Blast furnaces; Inorganic polymers; Neural networks; Palm oil; Slags; Titanium dioxide; Depollution; Dye removal; Energy source; Geopolymer; Green; Light irradiations; Methylene Blue; Methylene blue adsorption; Photo-catalytic; Research fields; Geopolymers